O PROCESSO DE APRENDIZAGEM DA LINGUAGEM MUSICAL POR MEIO DA BANDA DE MÚSICA: SOPRO E PERCUSSÃO - OLIVEIRA, Teotonio Rodrigues de (2024)
This article aims to present a teaching proposal that contributes to the learning processes of reading music for musicians participating in music bands. From this perspective, three specific objectives are listed: reflect on teaching music while participating in bands; describe the author's personal learning experience while working in bands; and build didactic strategies for teaching wind and percussion instruments in the context of a music band. The research methodology presents itself in the profile of a qualitative approach, and regarding the procedure, it is a research that is based on bibliography in the area of music and education, of the experience report type. Furthermore, the theoretical foundation is based on authors who address the study of musical theory and practice, as well as work with musical bands. That said, it is expected that the pedagogical proposal suggested for reading sheet music in a music band – wind and percussion instruments will enable beginner musicians, as well as those who play by ear, to read the music in a short space of time.